2013
DOI: 10.1002/cjoc.201300113
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Detection of pH‐responsive Drug Delivery System in Cells in situ by Confocal Laser Scanning Microscopy

Abstract: Mesoporous silica nanoparticles (MSN) were coated by pH-responsive polymer chitosan-poly (methacrylic acid) (CS-PMAA). This nano drug delivery system showed good application prospects and the polymer-coated microspheres were promising site-specific anticancer drug delivery carriers in biomedical field. A continuous detection of pH-responsive drug delivery system in cells in situ, utilizing MSN/CS-PMAA composite microspheres, was proposed. Two kinds of different cell lines, tumor cell line (Hela) and normal som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Finally, internalization studies carried out with HeLa cells indicated that coated nanoparticles were endocytosed and able to release entrapped DOX. Following their work, these authors used the same capped materials and suggested a new procedure to study pH-responsive delivery systems in cells in situ using CLSM . Two kinds of different cell lines, the tumor cell line (HeLa) and normal somatic cells (293T), were used.…”
Section: Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, internalization studies carried out with HeLa cells indicated that coated nanoparticles were endocytosed and able to release entrapped DOX. Following their work, these authors used the same capped materials and suggested a new procedure to study pH-responsive delivery systems in cells in situ using CLSM . Two kinds of different cell lines, the tumor cell line (HeLa) and normal somatic cells (293T), were used.…”
Section: Phmentioning
confidence: 99%
“…Following their work, these authors used the same capped materials and suggested a new procedure to study pH-responsive delivery systems in cells in situ using CLSM. 277 Two kinds of different cell lines, the tumor cell line (HeLa) and normal somatic cells (293T), were used.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…刺激响应型高分子材料是指一类可以通过外界环 境因素的刺激, 例如温度 [1] 、pH 值 [2,3] 、离子强度 [4] 、光 强度 [5] 等, 来改变自身物理化学性质的新型材料. 近年 来, 具有两亲性结构的刺激响应型高分子得到了广泛的 关注, 这主要是因为此类刺激响应型高分子材料不仅可 以自组装形成纳米尺寸和可作为纳米载体的胶束或聚 集体, 并且这类胶束或聚集体在外界因素刺激下可以对 增溶的分子进行可逆的释放或装载 [6] .…”
Section: 引言unclassified
“…As an emerging field, nanotechnology has been receiving great attention from researchers over the last few decades [1,2]. Due to its unique physical and chemical properties, nanomaterials with at least one dimension in the size of 1-100 nm have excellent optical, magnetic, mechanical, and catalytic properties in diverse fields [3][4][5][6]. Among the metallic nanoparticles (NPs), the silver nanoparticles (AgNPs) are widely used because of their strong antimicrobial efficiency [4,[7][8][9], optical functions [10], catalytic activity [9,11].…”
Section: Introductionmentioning
confidence: 99%